Interactions between Phosphoric/Tannic Acid and Different Forms of FeOOH - Lefu Mei; Libing Liao; Zise Wang; Chunchun Xu (Advances in Materials Science and Engineering)
Alpha, beta, gamma, and delta hydroxyl ferric oxides (FeOOH), as the most common rust layers on iron surface, play different roles in iron preservation. Using modern surface analysis technologies such as X-ray diffraction (XRD), infrared spectra (IR), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM), we studied the interactions between these four types of synthetic FeOOH and phosphoric and tannic acid of different concentrations and proportions. A 3% tannic acid + 10% phosphoric acid + FeOOH was the most suitable formula for rust stabilizer and its reaction products were made up of iron phosphate and chelate of iron and tannin. This research provided technical basis in distinguishing FeOOH and selecting rust layer stabilizer for the preservation of iron, especially iron cultural relics.